Ambivalence in narrative therapy: a comparison between recovered and unchanged cases - Ribeiro, António P. (2016)
Research on the identification of poor outcome predictors is crucial for the prevention of therapeutic failure. Previous research suggests that clients’ persistent ambivalence is one possible path to unsuccessful psychotherapy. The present study analyses ambivalence—here operationalized as return-tothe-problem markers (RPMs)—in five recovered and five unchanged cases of narrative psychotherapy for major depression. The results suggest that both recovered and unchanged cases presented a similar proportion of RPMs at baseline and a decreasing pattern of these ambivalence markers throughout therapy. However, the decreasing was more accentuated in recovered than in unchanged cases, and at the end of the treatment, the proportion of RPMs of the unchanged cases was significantly higher. The results are discussed in light of previous research on ambivalence in psychotherapy, focusing on the meaning of ambivalence and its clinical implications.